2022
DOI: 10.3126/josem.v1i2.45334
|View full text |Cite
|
Sign up to set email alerts
|

Ponds’ Water Quality Analysis and Impact of Heavy Metals on Fishes’ Body

Abstract: The anthropogenic activities have caused increase in the aquatic heavy metals pollution. The higher concentration of heavy metals in fish’s body also affects the consumers as it reaches to human body through the food chain. This study was conducted to analyze the ponds’ water quality based on physicochemical parameters and nutrients in relation to the dissolved heavy metals accumulated in the fishes’ body by using R programing. In this study, the heavy metals bio-accumulated from barrage pond and diversions po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Zinc is involved in many physiological functions, participates in building cells, helps in the growth and development of embryos, and is one of the basic factors for wound healing, but an increase in zinc beyond the permissible limits causes intestinal problems, anemia, and pancreatic damage [7]The results in Table (4) showed that the effect of the bi-interaction (type of fish and river location) of the study factors was that there were no significant differences (p≤0.05) in the values of zinc in all the studied fish samples taken from the Tigris River at the Samarra location, while the results of the biinteraction recorded ( Sample type and location) A significant increase (p≤0.05) in zinc, the highest value reached ((45.58 PPM) in Silurus triostegus fish taken from the Tigris River in the Tikrit location, and the highest value reached (18.10 PPM) in Nile tilapia fish taken from the Tigris River in the location Tikrit, and the average type of fish recorded a significant increase (p≤0.05) in zinc, with the highest value (36.34 PPM) in Silurus triostegus fish taken from the Tigris River, while its lowest value (23.28 PPM and 26.70 PPM) was recorded in Nile tilapia and Zari fish. Taken from the Tigris River respectively, these results did not agree with what was reported by [5] in Indonesia.As for the biinteraction (river location and sample type), no numerical differences were recorded, reaching the highest value, respectively (41.61 PPM, 38.97 PPM, 27.35 PPM, 34.55 PPM, 34.53 PPM, and 32.78 PPM) in the liver, muscles, and gills of fish. The lowest value was recorded in the intestines of the studied fish taken from the Tigris River at the Tikrit and Samarra locations.…”
Section: Zinccontrasting
confidence: 86%
See 2 more Smart Citations
“…Zinc is involved in many physiological functions, participates in building cells, helps in the growth and development of embryos, and is one of the basic factors for wound healing, but an increase in zinc beyond the permissible limits causes intestinal problems, anemia, and pancreatic damage [7]The results in Table (4) showed that the effect of the bi-interaction (type of fish and river location) of the study factors was that there were no significant differences (p≤0.05) in the values of zinc in all the studied fish samples taken from the Tigris River at the Samarra location, while the results of the biinteraction recorded ( Sample type and location) A significant increase (p≤0.05) in zinc, the highest value reached ((45.58 PPM) in Silurus triostegus fish taken from the Tigris River in the Tikrit location, and the highest value reached (18.10 PPM) in Nile tilapia fish taken from the Tigris River in the location Tikrit, and the average type of fish recorded a significant increase (p≤0.05) in zinc, with the highest value (36.34 PPM) in Silurus triostegus fish taken from the Tigris River, while its lowest value (23.28 PPM and 26.70 PPM) was recorded in Nile tilapia and Zari fish. Taken from the Tigris River respectively, these results did not agree with what was reported by [5] in Indonesia.As for the biinteraction (river location and sample type), no numerical differences were recorded, reaching the highest value, respectively (41.61 PPM, 38.97 PPM, 27.35 PPM, 34.55 PPM, 34.53 PPM, and 32.78 PPM) in the liver, muscles, and gills of fish. The lowest value was recorded in the intestines of the studied fish taken from the Tigris River at the Tikrit and Samarra locations.…”
Section: Zinccontrasting
confidence: 86%
“…The results showed that the lowest values For lead, (0.30 PPM and 0.81 PPM) were recorded in both zuri and Silurus triostegus taken from the Tigris River in the Tikrit location, and the average effect of fish type recorded a significant increase (p≤0.05) for lead, reaching (2.30 PPM and 1.70 PPM). In Nile tilapia and Aspius vorax, the lowest value was recorded (0.86 PPM) in zuri fish taken from the Tigris River.These results did not agree with [5] when they studied the level of heavy metal contamination in fish meat in different locations in Indonesia.…”
Section: Leadmentioning
confidence: 67%
See 1 more Smart Citation
“…Due to their toxicity, bioaccumulation, biomagnification, and persistence properties, metal contamination in water causes a significant impact on aquatic organisms (Mao et al, 2020). It has been emphasized that the bioaccumulated heavy metals by aquatic organisms have the tendency to biomagnify along the food chain and consequently pose a risk to the health of human consumers (Ndayisenga and Dusabe, 2022). A recent report established a strong correlation between the concentration of heavy metal levels in the fishpond and various tissues of the fish body (Leonard et al, 2022).…”
Section: -Introductionmentioning
confidence: 99%
“…It also serves as an essential source of water for various domestic, industrial, and agricultural purposes in the region (Ordoñez, 2013). However, the lake is facing significant environmental degradation due to rapid urbanization and industrialization, negatively affecting its physico-chemical and bacteriological characteristics (Serrano et al, 2019;Ndayisenga, & Dusabe, 2022).…”
Section: Introductionmentioning
confidence: 99%